2006
DOI: 10.1158/0008-5472.can-05-4398
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of CXCL5 Inhibits Squamous Carcinogenesis

Abstract: We report a novel role for the CXC-chemokine, CXCL5, in the proliferation and invasion of head and neck squamous cell carcinoma (HNSCC). Previously, we reported transcriptional up-regulation of CXCL5 in metastatic cells. In this study, we provide biological validation of these findings and show that CXCL5 is intimately involved in tumor cell proliferation, migration, and invasion. Cells derived from a lymph node metastasis, but not from a synchronous primary tumor, secreted CXCL5 as judged by Western blotting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 34 publications
5
91
0
1
Order By: Relevance
“…Generation of Cell LinesThat Stably ExpressVimentin shRNA HN12 cells containing vimentin shRNA (shVim) or nontargeting control (NTC) plasmids were prepared essentially as described (16). Cells were cultured to 60% confluency and then transfected with 3 Ag plasmid DNA using TransIT Keratinocyte Reagent (Mirus Bio).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of Cell LinesThat Stably ExpressVimentin shRNA HN12 cells containing vimentin shRNA (shVim) or nontargeting control (NTC) plasmids were prepared essentially as described (16). Cells were cultured to 60% confluency and then transfected with 3 Ag plasmid DNA using TransIT Keratinocyte Reagent (Mirus Bio).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative Real-time PCR Quantitative real-time PCR (qRT-PCR) was done using an ABI 7500 Fast system (Applied Biosystems) and a SYBR Green-based procedure as described previously (16). Oligonucleotide pairs for use as PCR primers (Supplementary Table S1) 7 were designed using the Primerbank Webbased database (17).…”
Section: Methodsmentioning
confidence: 99%
“…Microarray analysis for gene expression profiling in OSCC identified gene signatures that include chemokine (CXC motif) ligand-13 (CXCL13) that is implicated in OSCC development and progression (5). Recent evidence indicated that down-regulation of CXCL5 expression inhibits head and neck squamous cell carcinoma development and invasion (15). Therefore, we examined the potential of CXCL13 to modulate RANKL expression in OSCC cells.…”
Section: Cxcl13 Stimulates Rankl Expression In Oscc Cellsmentioning
confidence: 99%
“…Data suggest that CXCL5 enhances tumor development by stimulating proliferation, cell motility and invasion [107] as knockdown of CXCL5 by siRNA completely inhibited tumorigenicity in a mouse xenograft model.…”
Section: Oral Cavitymentioning
confidence: 99%
“…However, it is not yet confirmed if this observation is a consequence of secondary change as a result of gastric cancer progression, or whether it is one of the primary molecular events leading to tumor development. As CXCL5 is linked to tumor development in other organs [77,107,138] , further confirmation is needed through the use of in vitro and in vivo model systems in the future. Yanagie et al [139] performed a comparative analysis of differential gene expression related to chemokines/chemokine receptors and cytokines in established gastric cancer cell lines using a cDNA microarray approach.…”
Section: Stomachmentioning
confidence: 99%